The Canadian debt-strategy model: An overview of the principal elements - David Jamieson Bolder; Simon Deeley (Bank of Canada, 2011)
As part of managing a debt portfolio, debt managers face the challenging task of choosing a strategy that minimizes the cost of debt, subject to limitations on risk. The Bank of Canada provides debt-management analysis and advice to the Government of Canada to assist in this task, with the Canadian debt-strategy model being developed to help in this regard. The authors outline the main elements of the model, which include: cost and risk measures, inflation-linked debt, optimization techniques, the framework used to model the government's funding requirement, the sensitivity of results to the choice of joint stochastic macroeconomic term-structure model, the effects of shocks to macroeconomic and term-structure variables and changes to their long-term values, and the relationship between issuance yield and issuance amount. Emphasis is placed on the degree to which changes to the formulation of model elements impact key results. The model is an important part of the decision-making process for the determination of the government's debt strategy. However, it remains one of many tools that are available to debt managers and is to be used in conjunction with the judgment of an experienced debt manager.
Keywords: C0; G11; G17; H63; 330; Debt management; Econometric and statistical methods; Financial markets; Fiscal policy; Finanzmarkt; Öffentliche Schulden; Management; Finanzpolitik; Zentralbank; Kanada